2013
DOI: 10.1155/2013/956978
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy-Neural Ensemble and Geometric Rule Fusion Approach for Scheduling a Wafer Fabrication Factory

Abstract: In this study, the fuzzy-neural ensemble and geometric rule fusion approach is presented to optimize the performance of job dispatching in a wafer fabrication factory with an intelligent rule. The proposed methodology is a modification of a previous study by fusing two dispatching rules and diversifying the job slacks in novel ways. To this end, the geometric mean of the neighboring distances of slacks is maximized. In addition, the fuzzy c-means (FCM) and backpropagation network (BPN) ensemble approach was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The following dispatching methods were listed in a study by Wu and Chen [21]: dispatching rules; heuristics; data mining based approaches; agent technologies; and simulation. Moreover, the aforementioned work demonstrated that several studies have been conducted in an attempt to solve the problem of scheduling.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The following dispatching methods were listed in a study by Wu and Chen [21]: dispatching rules; heuristics; data mining based approaches; agent technologies; and simulation. Moreover, the aforementioned work demonstrated that several studies have been conducted in an attempt to solve the problem of scheduling.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, the aforementioned work demonstrated that several studies have been conducted in an attempt to solve the problem of scheduling. Regarding the approaches used in these studies, Wu and Chen [21] highlight the following: (i) selection of the most appropriate dispatching rule among those that are available; (ii) inclusion of adjustable parameters that can optimize the dispatching rule; and (iii) best estimate of the schedule through the results of a limited number of simulations. As for the approach (ii), it is emphasized that this can only be used with factors that are defined previously and remain static [21].…”
Section: Literature Reviewmentioning
confidence: 99%
“…(3) Generalized average method [30]: in FCM, the error is proportional to the distance to the center. For this reason, a natural way to aggregate the forecasts is…”
Section: Step 4: Establishing the Upper Bound For The Job Cyclementioning
confidence: 99%
“…The process stops after five iterations because the upper bounds remain unchanged after the fifth iteration. The results of the five iterations are summarized in Table 9, from which the allowances which are 25,33,54,48,56,57,58,44,54,53,42,46,55,48,47,50,48,41,36,39,30,41,31,24,34,29,27,13,37,24,47,15,34,50,44,49,53,50,53, and 53 added to the cycle times are derived with an average of 42 (hours). The due date of a job is then set to the release time plus the upper bound of the cycle time.…”
Section: Journal Of Applied Mathematicsmentioning
confidence: 99%
“…In wafer fabrication, a pattern of circuitry is imprinted onto the surfaces of a wafer, on which hundreds of dice are fabricated, and dice are individually tested in the process of wafer probe. In recent years, vast research of scheduling has been done in the field of wafer fabrication [1][2][3][4][5][6][7][8]. In [9,10] and the wafer probe process was scheduled as a mathematical model to minimize the makespan.…”
Section: Introductionmentioning
confidence: 99%